Peran Petugas Lembaga Rehabilitasi Dalam Membantu Korban Penyalahgunaan Narkotika di BNN Kabupaten Labura - Sitorus, Laura Isabela (JPUS: Jurnal Pendidikan Untuk Semua, 2022)
This study aims to determine the role of Rehabilitation Institute Officers in Helping Victims of Narcotics Abuse at the National Narcotics Agency (BNN) of Labura Regency. This research is a qualitative descriptive study with data collection techniques, namely observation, interviews and documentation to Labura Regency BNN officers, and data analysis techniques using an interactive model according to Miles and Huberman. The results showed that the role of rehabilitation agency officers in helping victims of narcotics abuse at the National Narcotics Agency (BNN) of Labura Regency, among others: (1) officers in prevention and community empowerment (P2M) as information desiminators, namely officers providing socialization and counseling to the community about the dangers of drug abuse; (2) officers in eradication as coordinators who are responsible for coordinating and encouraging the public in screening narcotics abuse syndicates to carry out investigations and investigations in realizing the P4GN program (prevention, eradication, abuse and illicit trafficking of narcotics); (3) rehabilitation officers, namely as facilitators by conducting screening tests in the form of assessment stages, urine tests, and motivational interviews. In this section, officers assist residents in maintaining drug-free conditions and restoring physical, psychological and social functions of drug users and abusers.